2013
DOI: 10.1063/1.4812345
|View full text |Cite
|
Sign up to set email alerts
|

Non-polar (11-20) InGaN quantum dots with short exciton lifetimes grown by metal-organic vapor phase epitaxy

Abstract: We report on the optical characterization of non-polar a-plane InGaN quantum dots (QDs) grown by metal-organic vapor phase epitaxy using a short nitrogen anneal treatment at the growth temperature. Spatial and spectral mapping of sub-surface QDs have been achieved by cathodoluminescence at 8 K. Microphotoluminescence studies of the QDs reveal resolution limited sharp peaks with typical linewidth of 1 meV at 4.2 K. Time-resolved photoluminescence studies suggest the excitons in these QDs have a typical lifetime… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
48
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 36 publications
(57 citation statements)
references
References 19 publications
9
48
0
Order By: Relevance
“…All calculations were performed on a 50 × 50 × 30-nm 3 supercell with periodic boundary conditions. With these assumptions, the calculated ground state transition energies were in the range of 2.7 to 2.9 eV, close to typical experimental values [27,32,33,[41][42][43][44] and those discussed below. Therefore, the chosen geometries and indium contents should give a reasonable description of the structures considered here.…”
Section: Theoretical Calculations Of Dolpmentioning
confidence: 53%
See 3 more Smart Citations
“…All calculations were performed on a 50 × 50 × 30-nm 3 supercell with periodic boundary conditions. With these assumptions, the calculated ground state transition energies were in the range of 2.7 to 2.9 eV, close to typical experimental values [27,32,33,[41][42][43][44] and those discussed below. Therefore, the chosen geometries and indium contents should give a reasonable description of the structures considered here.…”
Section: Theoretical Calculations Of Dolpmentioning
confidence: 53%
“…Previous studies on InGaN QD systems assumed lens-shaped geometries [39,40]. We followed this assumption, and based on earlier AFM results [33], chose a base diameter of 30 nm and a height of 2.5 nm as our starting point, with indium content varied between 15% and 25%. All calculations were performed on a 50 × 50 × 30-nm 3 supercell with periodic boundary conditions.…”
Section: Theoretical Calculations Of Dolpmentioning
confidence: 99%
See 2 more Smart Citations
“…6 Theoretical work has suggested that growth in the non-polar orientations may eliminate the in-plane electric field. 7 Previous work by Zhu et al 8 has demonstrated the growth of non-polar a-plane InGaN QDs by the modified droplet epitaxy (MDE) method with exciton lifetimes an order of magnitude smaller than comparable polar QDs, 9 and which exhibit improved temperature stability 10 and Rabi oscillations. 11 However, the photoluminescence (PL) linewidth of the QDs grown by MDE remains typically in excess of 1 meV.…”
mentioning
confidence: 99%